2023
DOI: 10.1001/jamanetworkopen.2023.17023
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Mask-Induced Cardiopulmonary Stress

Abstract: This randomized crossover trial evaluates the cardiopulmonary effects of extended use of the N95 mask during daily life.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…In healthy individuals, N95 masks cause minimal changes in blood gas and other physiological parameters during physical activity, even during very intense exercise [20]. A recent study of healthy volunteers suggested that even with mild exercise, prolonged wear of N95 masks can increase respiratory resistance, leading to a decrease in RR and SpO 2 within 1 hour and an increase in heart rate after 2 hours until the mask is removed [21]. Consistent with our research ndings, this study also did not nd any changes in BP, as healthy individuals can compensate for this cardiovascular overload.…”
Section: Discussionmentioning
confidence: 99%
“…In healthy individuals, N95 masks cause minimal changes in blood gas and other physiological parameters during physical activity, even during very intense exercise [20]. A recent study of healthy volunteers suggested that even with mild exercise, prolonged wear of N95 masks can increase respiratory resistance, leading to a decrease in RR and SpO 2 within 1 hour and an increase in heart rate after 2 hours until the mask is removed [21]. Consistent with our research ndings, this study also did not nd any changes in BP, as healthy individuals can compensate for this cardiovascular overload.…”
Section: Discussionmentioning
confidence: 99%
“…3,4 Wearing a mask may evoke many types of discomfort and lead to acute or chronic effects such as chest tightness, shortness of breath, anxiety, and palpitation. Bao et al 5 asked healthy individuals to continuously wear an N95 mask and observed the effects, which included a significantly increased heart rate after 1 hour of mask-wearing, significantly increased blood pressure (BP) after light exercise, and significantly increased plasma levels of norepinephrine and methoxyadrenaline after 14 hours of mask-wearing. It remains unclear whether wearing a mask for a long period can adversely affect BP in patients with hypertension and plasma glucose in those with diabetes, or whether mask-wearing makes it more challenging for these patients to control their BP and plasma glucose.…”
Section: Introductionmentioning
confidence: 99%